MODERN METHODS OF TEACHING PHILOSOPHY AT THE UNIVERSITY AND THEIR PEDAGOGICAL MEANINGS - Verle, Artem (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The dynamism and uncertainty of modern social life is a challenge for the entire education system and for philosophy as an educational discipline, in particular. The relevance of the work is associated with new requests for a new philosophical understanding of the world and life in university education. In this work, using theoretical analysis methods based on practical teaching experience, we propose an innovative approach to teaching philosophy as a technique and practice of public dialogical practice, built on the wonderment and rethinking of the ordinary and stereotypical. The purpose of this study is the theoretical and methodological justification of teaching methods of philosophy, oriented on the actualization of thinking here-and-now. The research methodology is based on a combination of general scientific theoretical methods and empirical methods of observation and comparison. The practice of applying the teaching methods described in the work is experimental. The development, testing and adjustment of the described philosophy teaching practices took place during the last 3 years of work at Pskov State University among first-year students of the undergraduate department of the Faculty of Finance and Economics. The complex use of this kind of techniques for students in philosophy classes in the experimental groups, in comparison with the results in the control groups, with other conditions being equal, yielded the following results: students in the experimental groups consistently showed better average results than students in control groups.